2020
DOI: 10.1155/2020/6239491
|View full text |Cite
|
Sign up to set email alerts
|

Combining Host Plant Resistance, Selective Insecticides, and Biological Control Agents for Integrated Management of Tuta absoluta

Abstract: Combination of pest management strategies that minimize pesticide use and conserve natural enemies is important for a sustainable environment. Overreliance on synthetic insecticides in the management of Tuta absoluta has led to pesticide resistance leading to difficulties in managing the pest. In this regard, alternative measures need to be put in place to reduce the effects of this pest. The objective of this study was, therefore, to assess the effectiveness of host plant resistance, biological control, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…As a significant agricultural pest in China (Pan et al, 2013 ), Apolygus lucorum (Meyer‐Dür) has caused increasing harm to wine and grape cultivation areas in recent years, becoming one of the most important control targets for grapes (Pan et al, 2021 ). Currently, most of the cultivation areas use broad‐spectrum chemicals to kill A. lucorum (Stevens et al, 2012 ), which pollutes the environment and also leaves residue that is harmful to humans and other animals (Wangari Nderitu et al, 2020 ). In the long term, the effective way to fundamentally limit the damage caused by A. lucorum is to improve the resistance of crops to pests, such as by identifying resistance genes and cultivating new resistant varieties (Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a significant agricultural pest in China (Pan et al, 2013 ), Apolygus lucorum (Meyer‐Dür) has caused increasing harm to wine and grape cultivation areas in recent years, becoming one of the most important control targets for grapes (Pan et al, 2021 ). Currently, most of the cultivation areas use broad‐spectrum chemicals to kill A. lucorum (Stevens et al, 2012 ), which pollutes the environment and also leaves residue that is harmful to humans and other animals (Wangari Nderitu et al, 2020 ). In the long term, the effective way to fundamentally limit the damage caused by A. lucorum is to improve the resistance of crops to pests, such as by identifying resistance genes and cultivating new resistant varieties (Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different management practices against it include cultural, physical, chemical attractants (such as pheromone), botanicals (such as neem-based products, jholmola homemade biopesticide and biofertilizer), and chemical pesticides. Although the use of chemical pesticides is the most commonly used control measure against TLM, the development of resistance against common pesticides can be a limiting factor to its effectiveness (Upreti et al, 2020;Wangari Nderitu et al, 2020). Cultural methods, including proper greenhouse structures, removing infected organs, and avoiding alternate host plants, may be necessary for managing TLM (Desneux et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the benefits of tillage could be temporary as long-term studies have shown degradation of soil structure, compaction, erosion of top soil, and extinction of soil-dwelling fauna as some of the consequences of it (Bhardwaj et al, 2016;Singh et al, 2020;Dey and Karmakar, 2021;Ghabeish et al, 2023). Other consequences of persistent use of conventional farming practices include depletion of natural resources (Kakraliya et al, 2018), biodiversity loss (Shaxson et al, 2008), environmental pollution (Stevens et al, 2012), and human health hazards (Nderitu et al, 2020). To minimize these negative impacts, particularly on soil and the environment, a new concept of farming called conservation agriculture (CA) took shape in the United States of America first and later spread throughout the world (Bhan and Behera, 2014).…”
Section: Introductionmentioning
confidence: 99%